IMPLEMENTASI MODEL PEMBELAJARAN FOCUS GROUP DISSCUSSION TEMA BJORKA DAN HACKER MATA PELAJARAN MATEMATIKA DI SMK NEGERI 1 PUJER: SMK NEGERI 1 PUJER - AGENG JELLY PURWANTO (Dewan Pendidikan Bondowoso, 2022)
The effects of a prolonged pandemic have made students rarely interact with each other so that students are more inclined to learn and find information individually. For this reason, a learning model is needed to overcome these conditions. SMKN 1 Pujer with class conditions without tables and chairs makes the teacher really have to choose a learning model that allows for a comfortable and conducive learning atmosphere. The chosen learning model is Focus Group Discussion. The choice of this learning model was due to the very supportive classroom conditions and student conditions. Besides that, the topic to be taken is also very supportive, namely the popularity of Bjorka in social media and television news. The type of research conducted is classroom action research using a qualitative approach with one learning cycle which includes, (1) planning, (2) implementation of action, (3) observation, and (4) reflection. The conclusion of this study is that the implementation of Focus Group Discussions in mathematics with the theme Bjorka and Hackers can increase students' interest in learning mathematics, this is because news about Bjorka attracts students' interest in learning hacking techniques so that it can become the basis for motivation to learn mathematics.